Analysis of Factors Affecting the Human Development Index in West Kalimantan Province using Data Panel Data Regression - Uray Hety Humaira; Jaka Nugraha (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
Development in the country is growing including in the West Borneo Province. However in 2015, the achievement of human development at the National level is quite low, while the District and City varied considerably. Human Development Index is one of the parameter for human development that are affected by many factors. In this paper, analysis for identify the factors for human development index in West Kalimantan Province by using Regression Analysis was conducted. Regression was based on time series data from 2012 until 2015. It is found that Fixed Effect Model is the best regression model with the R2 of 0.99853%. The influencing variables are Life Expectancy (AHH), Adjusted Per Capita (Expenditure), School Average (RLS), School Expectation (HLS), and Gross Regional Domestic Product at Constant Price (GRDP).